Institutional Innovation Performance of Tourism Villages: What Factors Are Needed? - Hamdan, Hamdan; Krisnahadi, Tama; Komaria , Nur; Ilhamalimy, Ridho Rafqi; Raharja, Indra (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
The Province of West Nusa Tenggara (NTB), Indonesia, has significant potential for developing tourism village. However, improving the institutional performance of tourism village requires greater attention, particularly in driving innovation. This research focuses on the influence of digital leadership, collaboration strategy, and market orientation on innovation performance, with government support as a moderating variable through a community-based tourism approach known as Pokdarwis. A quantitative method using SEM analysis was applied, with a specific sample of the developing and advanced tourism villages to effectively assess institutional performance. The results of the study found that digital leadership, collaboration strategy, and market orientation positively and significantly influenced innovation performance. However, the relationship between digital leadership, government support, and innovation performance, as well as the moderation effect, was not significant. This research offers strategic policy recommendations to support effective decision-making in rural tourism development. The inconsistency of digital leadership highlights the need for further research, considering the growing trend of digital transformation. Further details are discussed in this study.